PENGARUH PENERAPAN MODEL PEMBELAJARAN QUANTUM TEACHING TERHADAP KEMAMPUAN KOMUNIKASI MATEMATIS PESERTA DIDIK KELAS VIII SMP ISLAM AL-ISLAH BUKITTINGGI - Nisa Khalistha (Departemen Matematika, 2021)
The abilitis that are expected t0 be p0ssessed by students leaning mathematics, one of which is mathematical communication. H0wever, in reality, from the learning outcomes 0f student, it cann be seen that the matematical communication 0f grade VIII students of Islamic Junior High School Al-Islah Bukittinggi is still l0w, s0 it must be impr0ved. One 0f the efforts made to improve students' mathematical communication skills is by implementing a learning model that facilitates students to learn actively and build their own knowledge. The learnning model that can be applied is the Quantum Teaching model. Based on these problems, a study was conducted to see whether the mathematical communication application 0f students wh0 learn with the Quantum Teaching leaning m0del is beter at learning with conventional learning in class VIII of SMP Islam Al-Islah Bukittinggi. Keywords – Quantum Teaching, Mathematical Comunication Skill.